2020
DOI: 10.1002/chem.202002799
|View full text |Cite
|
Sign up to set email alerts
|

A Sterically Hindered Derivative of 2,1,3‐Benzotelluradiazole: A Way to the First Structurally Characterised Monomeric Tellurium–Nitrogen Radical Anion

Abstract: DedicatedtoProfessor Rosa Llusaro nt he occasiono fh er birthdaya nd in recognition of her inspiring combinations of chemical experiment and quantum theory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 132 publications
1
12
0
Order By: Relevance
“…This approach recently demonstrated complete agreement with experiment for the HFS tensor of 125 Te in a tellurium-containing radical anion. 50 For complex 1, these accurate calculations predicted an anisotropic g-tensor with g iso = 2.135 (see the SI for details) with good agreement with experiment (g iso = 2.115). As expected from the spin density distribution and the SOMO shape (Figure 3), the HFS tensors and constants are close for three rhenium atoms with |a iso ( 187 Re)| equal to 9.67, 9.91, and 11.74 mT for Re1−Re3, respectively (Table S1).…”
Section: ■ Results and Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This approach recently demonstrated complete agreement with experiment for the HFS tensor of 125 Te in a tellurium-containing radical anion. 50 For complex 1, these accurate calculations predicted an anisotropic g-tensor with g iso = 2.135 (see the SI for details) with good agreement with experiment (g iso = 2.115). As expected from the spin density distribution and the SOMO shape (Figure 3), the HFS tensors and constants are close for three rhenium atoms with |a iso ( 187 Re)| equal to 9.67, 9.91, and 11.74 mT for Re1−Re3, respectively (Table S1).…”
Section: ■ Results and Discussionsupporting
confidence: 53%
“…The spin-Hamiltonian parameters were calculated using the exact two-component relativistic X2C method with a self-consistent account of spin–orbit coupling (SOC), as described in the Computational Details section. This approach recently demonstrated complete agreement with experiment for the HFS tensor of 125 Te in a tellurium-containing radical anion . For complex 1 , these accurate calculations predicted an anisotropic g -tensor with g iso = 2.135 (see the SI for details) with good agreement with experiment ( g iso = 2.115).…”
Section: Resultsmentioning
confidence: 52%
“…The four-coordinate tellurium radical anion Te-A1 (Scheme 107), the first stable tellurium-nitrogen radical anion, was synthesized via the one-electron reduction of Te-PA1 with Cp 2 Co. 157 The solution EPR spectrum of Te-A1 at room temperature reveals a five-line pattern at g = 1.9948 and a( 14 N) = 0.50 mT. After cooling to 153 K, two weak satellites separated by 29.0 mT were observed in the solution EPR spectrum of Te-A1, which correspond to the hyperfine coupling with the 125 Te nuclei (a zz ( 125 Te) = 29.0 mT).…”
Section: Anionic Radicalsmentioning
confidence: 99%
“…Thus, the spin-Hamiltonian parameters for 3 were calculated using the exact two-component relativistic X2C method with self-consistent consideration of spin-orbit coupling (SOC) in conjunction with the B3LYP functional and relativistic STO-type basis set. Recently, [14] it was demonstrated that the same computational approach applied for the nearest neighbor of iodine in the periodic table ( 125 Te) leads to complete agreement with the experiment. In support of this choice, it should also be noted that P. Haase et al [15] recently reported that the use of both the two-component X2 C and four-component Dirac-Coulomb Hamiltonians yields practically identical results for other neighbors of 127 I: 137 Ba and 133 Cs.…”
Section: Resultsmentioning
confidence: 74%
“…The calculations were carried out for two optimized geometries (3-1' and 3-2'). The results [g iso , hyperfine coupling (HFC) tensors (A) and constants (a iso ) with 127 I as well as with 14 N] are presented in Table 2. Slightly different HFC constants (0.54 and 0.6 mT) were predicted for two nitrogen atoms; both calculated values somewhat underestimate the typical values in nitronyl nitroxides (~0.75 � 0.04 mT), [16][17][18] which is typical of UB3LYP calculations.…”
Section: Resultsmentioning
confidence: 99%